Awareness and Associated Correlates of Contraception Use among Patients of Reproductive Age: A Cross-sectional Analysis at Jinnah Postgraduate Medical Centre, Karach - Syeda Zehra Haider; Tafazzul Hyder Zaidi; Benish Sajid; Summaiya Haider; Rizwana Tabassum; Mishal Jafry; Sunila Saleem; Kiran Abbas (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the level of awareness of contraception among patients of reproductive age groups.